2018
DOI: 10.1161/cir.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behaviors in Today’s Youth: Approaches to the Prevention and Management of Childhood Obesity: A Scientific Statement From the American Heart Association

Abstract: This scientific statement is about sedentary behavior and its relationship to obesity and other cardiometabolic outcomes in youth. A deleterious effect of sedentary behavior on cardiometabolic health is most notable for screen-based behaviors and adiposity; however, this relation is less apparent for other cardiometabolic outcomes or when sedentary time is measured with objective movement counters or position monitors. Increasing trends of screen time are concerning; the portability of screen-based devices and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
138
4
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 171 publications
5
138
4
10
Order By: Relevance
“…Although we found limited evidence for associations between lifestyle habits or fitness and the risk of developing the NWMU phenotype, our findings point towards the detrimental impact of increasing screen time from childhood to early adolescence on cardiometabolic health, even among normal weight children [38]. Moreover, baseline physical activity, but not 2-year changes in physical activity, was marginally protective against the risk of developing the NWMU phenotype.…”
Section: Discussioncontrasting
confidence: 68%
“…Although we found limited evidence for associations between lifestyle habits or fitness and the risk of developing the NWMU phenotype, our findings point towards the detrimental impact of increasing screen time from childhood to early adolescence on cardiometabolic health, even among normal weight children [38]. Moreover, baseline physical activity, but not 2-year changes in physical activity, was marginally protective against the risk of developing the NWMU phenotype.…”
Section: Discussioncontrasting
confidence: 68%
“…25 These are well-known risk factors for developing overweight and obesity in children and adolescents. [26][27][28][29] Interestingly, these behavioral characteristics were more common among high school students, which is in line with the rapidly increased prevalence of obesity in the same population group.…”
Section: Characteristics Of Obesity In Korean Children and Adolescentssupporting
confidence: 62%
“…Recent reports indicated that 99% of adolescents in Spain had a mobile phone [66], which could explain why its use is not associated with healthy behavior. Considering the breakthrough of new technologies in developed countries, practitioners and policy-makers should reconsider the development of new sedentary screen time recommendations for each screen-based sedentary behavior [67].…”
Section: Discussionmentioning
confidence: 99%